Sintering behaviour, microstructural characterisation and thermal expansion properties of Sn substituted ZrMo2O8. Issue 2 (1st February 2018) - Ramamurthy, Jayanth R.; Johnson, Roy; Kumar, Ravi
Abstract: The coefficient of thermal expansion (CTE) of ZrMo2 O8 can be fine-tuned by controlling the amount of tin substitution in zirconium lattice sites. The sintering challenges associated with this material and the optimal sintering conditions were investigated in this study. Powders of tin substituted ZrMo2 O8 were synthesised by co-precipitation technique. X-ray diffraction studies confirmed the formation of cubic SnMo2 O8 . Sintered pellets were produced from the powders and optimal sintering without decomposition of the phase was achieved at the expense of porosity. The material was found to be thermally stable up to 600 °C using thermogravimetric analysis. Dilatometric analysis of the sintered compacts shows that the CTE of the sample is in the order of 3.9 × 10 −6 /K, between 25 °C and 600 °C.